"Men in the Sun" by Ğassân Kanafani - Paić-Vukić, Tatjana (Prilozi za orijentalnu filologiju, 2017)
The novel "Men in the Sun” by the Palestinian writer Gassân Kanafinl dramatizes the attempt ofa group of Palestinian refugees to enter Kuwait ille- gally, hidden in an empty water tank and their death at the border Crossing. The novel has been subject to many, mostly allegoric interpretatioirs based on lin- king the text with its historical context. It was understood as a sharp criticism oftheArab world’s attitude toward the Palestinians in a decade following their plight from their homeland. As for stylistic featrrres of the novel, there are some differences in the critics’ opinions. Some consider it a traditional realistic novel, while others place it in the stream ofmodernism inspired by the great Anglo-American modernistic works. By the time ofits writing the novel stands on the border bebveen the two important phases of the Arabic novel. I. e. at the point where the traditional re- alism which dominated in tire fifties is being pushed aside by experimental 1İ- terary devices. Its main characteristics - mimesis, referentiality, psychological and social motivation ete., are inherent to realistic fiction, but it bears many de- vices which break with the narrative tradition ofthe fifties. These are: the direct interior monologue in which the inner experience ofthe fictional character is presented without the authorial mediation, free indirect speech - third person narration which transmits the thoughts/speech ofthe character, subjective expe- rience, the past and the present blend in the principle ofassociations and with- out authorial interventions and the limitation ofthe narrator’s omniscience in the point ofculmination. In this novel, the most frequent mode of transmitting the characters thoughts and presenting their past is free indirect speech rvhich is one ofthe main devices ofnrodem realistic fiction. It can be concluded that tire novel "Men in the Sun” is a modem realis- tic fictional work which breaks with the tradition of tire fifties, but is not a mo- demistic novel since only "the larger quantities ofthe interior monologue con- stitrrte modernistic fictional rvorks”. In his next novel, "Ali that's left for you”, Kanafönl will reach the end of his way towards modernism, by making the in- terior monologue the basic narrative strategy.